PEMANFAATAN MODEL PJBL DENGAN MEDIA POP UP UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS V SD NEGERI 19 BANDA ACEH - Nailul, Nailul Autari; Lili Kasmini; Tria Marvida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to find out whether the use of the PJBL model with Pop Up media on what on earth we can improve the learning outcomes of IPAS for elementary school students. This study uses a quantitative approach with an experimental method in the form of one group pretest-posttest design. The subject of the study was a grade V student of SDN 19 Banda Aceh. The data collection technique is carried out by administering pretest and posttest tests. The results of the normality test using Shapiro-Wilk showed that the significance value for the pretest data was 0.062 and for the posttest was 0.098. Since both values are greater than 0.05, it can be concluded that the data is normally distributed. This suggests that the data deserves to be analyzed more. And the results of the Paired Sample Test test data to see the difference in pretest and posttest results. A significance value of 0.00 (≤ 0.05) was obtained and an average increase of 18.333. The conclusion of this study is that the use of the PJBL model with Pop Up media is effective in improving student learning outcomes